2022
DOI: 10.3390/ani12101244
|View full text |Cite
|
Sign up to set email alerts
|

Confounding Rules Can Hinder Conservation: Disparities in Law Regulation on Domestic and International Parrot Trade within and among Neotropical Countries

Abstract: Wildlife trade is a major driver of biodiversity loss worldwide. To regulate its impact, laws and regulations have been implemented at the international and national scales. The Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES) has regulated the international legal trade since 1975. However, an important volume of illegal trade—mainly within countries—continues to threaten several vertebrate groups, which could be due to a lack of specific legislation or enforcement of exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…Marsden & Royle, 2015;Tella et al, 2021). Following Romero-Vidal et al (2020), we choose roadside surveys since this methodology allows to sample very large areas to increase the likelihood of recording parrots showing low densities and/or patchy distributions (Dénes et al, 2018;Tella et al, 2021). Using this methodology, the number of individuals recorded strongly correlates (r = .93) with density estimates accounting for differences in detectability among species (i.e., through distance-sampling modeling), and allows the calculation of relative species-specific abundances (individuals/km) for whole parrot communities, including the scarcer species that yield insufficient encounters for modeling detectability (see further details, strengths, and weakness of this method in Tella et al, 2021).…”
Section: Relative Parrot Abundances In the Wildmentioning
confidence: 99%
See 2 more Smart Citations
“…Marsden & Royle, 2015;Tella et al, 2021). Following Romero-Vidal et al (2020), we choose roadside surveys since this methodology allows to sample very large areas to increase the likelihood of recording parrots showing low densities and/or patchy distributions (Dénes et al, 2018;Tella et al, 2021). Using this methodology, the number of individuals recorded strongly correlates (r = .93) with density estimates accounting for differences in detectability among species (i.e., through distance-sampling modeling), and allows the calculation of relative species-specific abundances (individuals/km) for whole parrot communities, including the scarcer species that yield insufficient encounters for modeling detectability (see further details, strengths, and weakness of this method in Tella et al, 2021).…”
Section: Relative Parrot Abundances In the Wildmentioning
confidence: 99%
“…Moreover, these figures surely underestimate the actual extraction rates, as they do not account for the high mortality during capture, transport, and captivity before and after selling wildcaught birds (Baños-Villalba et al, 2021;Gonz alez, 2003) neither for the high percentage of poached parrots that remains undetected during surveys (Gastañaga et al, 2011). Furthermore, these surveys were mostly restricted to markets located in large cities and thus field studies aimed at estimating the number of parrots removed for self-supply or sold by poachers on a more local scale in rural areas, which could largely outnumber parrots sold in city markets (Romero-Vidal et al, 2020), are needed (S anchez-Mercado et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the laws and regulations regarding the legal and illegal aspects of this trade are often confusing and contradicting between national and international levels. Romero-Vidal et al [ 8 ] made the first attempt to disentangle such regulations regarding the domestic and international wildlife trade in Neotropical countries, specifically focusing on the trade and possession of parrots. They found that among 46 Neotropical countries/territories with native parrot populations, only Suriname and Guyana currently allow the capture, trade, and possession of these parrots, while Suriname, Guyana, and Peru also allow legal international trade.…”
Section: Law and Wildlife Tradementioning
confidence: 99%
“…Given the risks associated with wildlife trade, many traded taxa are regulated to prevent population declines and extinctions, where the primary regulatory body for international wildlife trade is the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES, 2023). While individual countries have their own domestic policies for wildlife trade occurring within their borders, not all wildlife trade is regulated (Romero‐Vidal et al, 2022). In terms of international trade, less than 10% of all known plant and terrestrial vertebrate species, and less than 1% of all known fish and invertebrate species, are listed on CITES.…”
Section: Introductionmentioning
confidence: 99%